Archaeological, Literary and Ethnographic Evidence for Traditional Boat-building in Kerala, South India - Veerasamy Selvakumar
Kerala possesses rich maritime traditions dating back to the Early Historic p eriod. A few types of traditional watercrafts developed indigenously and some are influenced by external contacts. Archaeological excavations revealed a medieval sailboat at Kadakkarappally in 2003 and an Early Historic canoe at Pattanam in 2007. The Early Historic Sangam Tamil texts refer to the watercrafts of Kerala. Traditional boat-building still survives in Kerala. This paper presents the evidence for traditional boats in Kerala, their historical context and the possible external 2 influences, until the 15th century Common Era (CE).